PEMBUATAN KUE KAPIT SARI DAUN LIDAH BUAYA ( Aloe vera L. ) SEBAGAI PRODUK ALAMIAH INOVATIF SIAP KONSUMSI BAGI MASYARAKAT NON AGRARIS UNTUK MENJAGA KESEHATAN LAMBUNG - Haque, Monalisa Fadhilah; Putra, Risa Kota; Ratnasari, Dewi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: Aloe vera (Aloe vera L.) is a plant that is commonly used by the community to treat gastric ailments, but the use of aloe vera in the form of extract is less practical, easily damaged and low acceptability. So there is a need for innovative, practical and durable preparations for storage. Research Objectives: This study aims to provide innovative natural products in the form of aloe vera L. (Aloe vera L.) leaf juice to maintain healthy stomach so that it is easy to consume, practical and easy to carry everywhere by non-agricultural communities. Method: This research was conducted by the action research method. This research was made by mixing 150 grams of Aloe vera juice (Aloe vera L.), 150 gr rice flour, 50 gr sago flour, one egg, 100 gr sugar, 0.3 gr salt and three variations of the amount of coconut milk that different. Variations in the composition of coconut milk used are 30 mL, 80 mL, and 130 mL. Results: The composition variation results that most meet the criteria of capitite cake criteria and the level of fragility that is with the addition of 80 mL coconut milk from the amount of 400 mL batter. Organoleptic testing of preparations carried out for 21 days at a temperature of 25 ° C includes odor, shape, taste, texture, color and growth of mushrooms, the results of organoleptic testing of aloe vera leaf capitale leaf cake capitals (Aloe vera L.) are relatively stable, no changes and no mold growth for 21 days. Conclusion: The conclusion from this study found that the best criterion is F2 with the addition of 80 mL coconut milk from the amount of 400 mL material showing the content of 9.37 grams of aloe vera which can last for three weeks.